Promoting teachers' wellbeing through a serious game intervention: a qualitative exploration of teachers' experiences - Cavioni, Valeria; Conte, Elisabetta; Ornaghi, Veronica (Frontiers in Psychology, 2024)
Introduction Teachers' wellbeing plays a critical role in their overall job satisfaction, motivation, and effectiveness in building supporting learning environments. In today's dynamic educational settings, where teachers often face numerous challenges and stressors, their wellbeing becomes increasingly vital. Consequently, there is an urgent need to innovate and develop targeted training interventions that can support specifically the wellbeing of educators. Methods This study sought to provide an overview of the “Online Wellbeing Course - OWC,” a serious game developed to enhance teachers' wellbeing, and to investigate the participants' feedback after being engaged in the OWC, utilizing a qualitative approach through focus group discussions. A total of 189 in-service teachers took part in the study. To qualitatively explore their experiences with the OWC, participants were involved in focus groups and asked to provide feedback about how and to what extent the course was beneficial for their wellbeing. Results Teachers reported enhancements in areas such as emotional competence, self-care strategies, social awareness, relationship skills, decision-making, and school climate. Discussion These outcomes suggested the potential of serious games as an innovative training approach for supporting teachers' wellbeing, offering valuable insights for researchers, policymakers, and educators.